Development of Guided Discovery Learning-Based Reaction Rate Student Worksheets Integrated with Ethnoscience to Support Deep Learning - Alya Fitri; Nofri Yuhelman (Universitas Lampung, 2026)
Developing Guided Discovery Learning-Based Reaction Rate Worksheet Integrated with Ethnoscience Oriented to Deep Learning Principles. This study aims to develop a reaction rate student worksheet (LKPD) based on guided discovery learning integrated with ethnoscience, and to determine its validity and practicality in supporting deep learning principles at SMA/MA. This development research applied the 4D model (Define, Design, Develop, Disseminate). The subjects of this study were students of class XI F 2 at SMAN 16 Padang. Data were collected using preliminary study instruments (teacher interviews and student need questionnaires), validity instruments (expert validation sheets), and practicality instruments (teacher and student response questionnaires). The developed worksheet achieved a high validity score of V = 0,93 (valid category). The practicality tests by the teacher and students yielded scores of 93% and 84%, respectively, both falling into the highly practical category. Furthermore, the implementation of this worksheet successfully helped students improve their deep learning principles. The guided discovery learning-based reaction rate worksheet integrated with ethnoscience can be successfully developed using the 4D model, meets the valid criteria, is highly practical for chemistry learning, and effectively enhances students' deep learning principles.